Search, Liquidity, and Retention: Screening Multidimensional Private Information - Williams, Basil (Journal of Political Economy, 2021)
A large literature has shown that asset quality may be signaled by retention or, in a separate literature, screened by liquidity. I present a general framework to analyze both instruments, offering conditions that characterize which instrument will be used in equilibrium. I then expand the private information to include not only asset quality but also seller patience, showing that both retention and liquidity may be used to fully separate both dimensions of private information. The expanded model offers new predictions about how price, quantity, and liquidity covary with each other and with seller private information.